2005
DOI: 10.1055/s-2004-821052
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Week Traditional Altitude Training Increases Hemoglobin Mass and Red Cell Volume in Elite Biathlon Athletes

Abstract: It is well known that altitude training stimulates erythropoiesis, but only few data are available concerning the direct altitude effect on red blood cell volume (RCV) in world class endurance athletes during exposure to continued hypoxia. The purpose of this study was to evaluate the impact of three weeks of traditional altitude training at 2050 m on total hemoglobin mass (tHb), RCV and erythropoietic activity in highly-trained endurance athletes. Total hemoglobin mass, RCV, plasma volume (PV), and blood volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
81
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(90 citation statements)
references
References 25 publications
3
81
1
2
Order By: Relevance
“…The relative increase (compared to non-responders) in the current study in SpO 2 in responders (which corroborates the theory of Chapman et al could be explained in part by increased haemoglobin concentration [30], enhanced erythropoietic response [7,31], which may result in increased red cell volume [4] and subsequently increased arterial oxygen content. Weil et al noted a graded response such that an increase in red cell mass was proportional to oxyhaemoglobin saturation at sea level and altitude [32].…”
Section: Citation: Hamlin Mj Manimmanakorn a Creasy Rh Manimmanakosupporting
confidence: 91%
See 2 more Smart Citations
“…The relative increase (compared to non-responders) in the current study in SpO 2 in responders (which corroborates the theory of Chapman et al could be explained in part by increased haemoglobin concentration [30], enhanced erythropoietic response [7,31], which may result in increased red cell volume [4] and subsequently increased arterial oxygen content. Weil et al noted a graded response such that an increase in red cell mass was proportional to oxyhaemoglobin saturation at sea level and altitude [32].…”
Section: Citation: Hamlin Mj Manimmanakorn a Creasy Rh Manimmanakosupporting
confidence: 91%
“…The other possible cause for lower heart rates in responders during submaximal exercise may be due to increased vagal dominance [14], or to the elevation of red cell volume, therefore blood volume, stroke volume and ultimately cardiac output, which subsequently decreases heart rate. A recent study demonstrated that red cell volume remained elevated in responders after 2 weeks of altitude training, while non-responders red cell volume returned to their original levels [4]. However, such linkages between heart rate changes and response to altitude require further research to confirm findings.…”
Section: Citation: Hamlin Mj Manimmanakorn a Creasy Rh Manimmanakomentioning
confidence: 95%
See 1 more Smart Citation
“…Three -four weeks at moderate altitude is the minimal recommended period required to maximize the erythropoietic response (Chapman and Levine 2007;Heinicke et al 2005). …”
Section: Introductionmentioning
confidence: 99%
“…Wilber (2004) and Millet and Schmitt (2012) state that the best thing for peak endurance athletes is permanent residence at an altitude of 1800 to 2300 m above sea level (ASL). If a permanent move to such an altitude is not possible, then Levine and Stray-Gundersen (1997) and Heinicke, Heinecke, Schmidt, and Wolfarth (2005), for example, consider it optimal to repeat altitude training camps several times over the course of the annual training cycle with a minimum length of 21 days due to the course of acclimatisation. This length is optimal, but due to socioeconomic reasons it is not always possible (Suchý & Dovalil, 2009).…”
Section: Introductionmentioning
confidence: 99%